2013
DOI: 10.1016/j.jhin.2012.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Patient narratives of surgical site infection: implications for practice

Abstract: SSIs have a low profile among patients which, if it were raised, could increase compliance with preventive interventions. This study confirms the appropriateness of using patient self-assessment post-discharge surveillance questionnaires to identify SSI symptoms, and highlights the need to identify total costings including to primary care, patients and the economy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 9 publications
1
34
0
Order By: Relevance
“…1 Therefore, those hospitals which conduct high-quality, rigorous surveillance of SSIs (and which therefore are more likely to identify more cases of infection) are likely to be penalized within the current surveillance service. 21 This further exacerbates the cost to the service which provides the initial surgical treatment.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Therefore, those hospitals which conduct high-quality, rigorous surveillance of SSIs (and which therefore are more likely to identify more cases of infection) are likely to be penalized within the current surveillance service. 21 This further exacerbates the cost to the service which provides the initial surgical treatment.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…While the informed consenting process for surgery should involve a discussion around the risk of SSI, very few patients appear to be concerned about this complication prior to their operation. 21 However, the impact on the quality of life of patients, families and carers who do experience SSI is likely to be substantial. This is perhaps magnified in spinal tumour patients given the clinical implications of SSI after this type of surgery (i.e.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…In-depth qualitative research has revealed that surgical site infections were perceived by patients to be as a result of chance or as a result of their own neglect in post-operative care; MRSA conversely was viewed as avoidable and hence the result of deficiencies in hospital management and care. 10 Users are exposed to a lot of information and indicators about rates of hospital acquired infections via hospital websites as well as the media but we don't know how users …”
Section: Introductionmentioning
confidence: 99%
“…[1] The implementation of innovations for surgical care within the operating room (OR) context has been massive over the last 100 years and can be described in many ways as a life-saving success. How-ever, unintended harm from surgery such as postoperative infections are preventable complications that cause unnecessary patient suffering [2][3][4] and deaths. [5,6] Results from the Harvard Medical Practice Study II [7] showed that nearly half (48%) of the errors in medical practice were related to surgical procedures, most of which occurred in the OR.…”
Section: Introductionmentioning
confidence: 99%